MODEL PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN HASIL BELAJAR IPAS - Khairunnisa, Nadiyah; Syofyan, Harlinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low academic achievement of fifth-grade students at SDN Duri Kosambi 07 Pagi in IPAS motivated this research. To address this issue, the study aimed to enhance students learning outcomes by applying a project based learning approach that utilizes the school environment. This research was conducted using using Classroom Action Research (CAR) based on the Kemmis and Taggart model over two cycles. Results indicated significant improvements in students mastery of the material throughout both cycles. In cycle I, the pre-test showed 37,5% of students meeting the mastery criteria with an average score of 64,33, while the post-test increased to 50% completeness and an average score of 70,96. In cycle II, the pre-test revealed 64,29% mastery with an average of 69,96, which further improved in the post-test to 85,71% completeness and average score of 87,32. These findings demonstrate that implementing a project based learning model based on school environment utilization can effectively improve the IPAS learning outcomes of fifth-grade students at SDN Duri Kosambi 07 Pagi.